Factors associated with depression and anxiety in children with intellectual disabilities - Whitney, Daniel G. (J Intellect Disabil Res, 2018)
BACKGROUND: Individuals with intellectual disabilities (ID) are at increased risk for depression and anxiety disorders; however, there is a paucity of research that pertains to associative factors for these mental health disorders in this population. The objective of this investigation was to determine factors associated with depression and anxiety problems in children with ID. METHOD: Children 6-17 years with ID (n=423; 63% male) from the 2016 National Survey of Children’s Health were included in this cross-sectional study. Outcome measures included depression and anxiety problems. Predictor variables included sociodemographics, ID severity, comorbid conditions (autism spectrum disorders [ASD], epilepsy, cerebral palsy, Down syndrome, and attention-deficit hyperactivity disorder [ADHD]), physical factors (i.e., physical activity, sleep duration, and pain), and social factors (e.g., participation in activities and bully victimization). Multivariable logistic regression was performed to determine the association between all factors and depression and/or anxiety problems among children with ID. RESULTS: The prevalence of depression and/or anxiety problems was 35.4%. After adjusting for sociodemographics, Hispanic race was associated with lower odds (odds ratio [OR], 0.3; 95% confidence interval [CI], 0.1-0.8) of depression and/or anxiety problems. After adjusting for race, comorbid conditions, and physical and social factors, ASD (OR, 4.4; 95% CI, 1.1-10.1), Down syndrome (OR, 0.2; 95% CI, 0.1-0.8), ADHD (OR, 5.9; 95% CI, 2.5-14.3), pain (OR, 7.0; 95% CI, 2.9-17.1), and bully victimization (OR 2.3; 95% CI, 1.0-5.3) were each associated with depression and/or anxiety problems. CONCLUSIONS: The present study identified both treatable or modifiable, as well as unmodifiable factors associated with depression and/or anxiety problems in children with ID.